The impact of ancient Mesoamerican cities on long-term environmental sustainability: the view from historical ecology - Antorcha-Pedemonte, Ricardo; Rivera-Núñez, Tlacaelel; Fargher-Navarro, Lane F. (Frontiers in Ecology and Evolution, 2023)
The impact of ancient urban occupations on sustainability has recently become a topic of interest for archaeologists as well as many other scholars. Much of this archaeological research has focused on documenting the longevity of ancient cities and elucidating the social and economic strategies employed at the urban and regional scales to promote urban sustainability. In this article, we add to this discussion by addressing the issue of sustainability by considering the impact of environmental legacies left by ancient cities after their abandonment. Using a series of cases from pre-Hispanic Mesoamerica [OMYK (Coba), Kiuic, Lagunas de Yalahau, and Tlaxcallan], we show through ethnoecological and historical ecological research that in some cases pre-Hispanic people, living in urban zones, affected “intermediate” disturbances that increased biodiversity, biomass, and sustainability by creating second natures that have endured for centuries.